For profit eaudiobook A history of corporations. - Magnuson, William (2022)
A history of how corporate innovation has shaped society, from ancient Rome to Silicon Valley Americans have long been skeptical of corporations, and that skepticism has only grown more intense in recent years. Meanwhile, corporations continue to amass wealth and power at a dizzying rate, recklessly pursuing profit while leaving society to sort out the costs.   In For Profit , law professor William Magnuson argues that the story of the corporation didn't have to come to this. Throughout history, he finds, corporations have been purpose-built to benefit the societies that surrounded them. Corporations enabled everything from the construction of ancient Rome's roads and aqueducts to the artistic flourishing of the Renaissance to the rise of the middle class in the twentieth century. By recapturing this original spirit of civic virtue, Magnuson argues, corporations can help craft a society in which all of us—not just shareholders—benefit from the profits of enterprise.